An Overview of Hormone-Sensitive Lipase (HSL) - Arwa R. Althaher (The Scientific World Journal)
Hormone-sensitive lipase (HSL) is a pivotal enzyme that mediates triglyceride hydrolysis to provide free fatty acids and glycerol in adipocytes in a hormonally controlled lipolysis process. Elevated plasma-free fatty acids were accompanied by insulin resistance, type-2 diabetes, and obesity. Inhibition of lipolysis through HSL inhibition may provide a mechanism to prevent the accumulation of free fatty acids and to improve the affectability of insulin and blood glucose handling in type II diabetes. The published studies that examine the structure, regulation, and function of HSL and major inhibitors were reviewed in this paper.